Hepatocellular Carcinoma: Frequency and Risk Factors at a Tertiary Care Hospital - Mujahid All Chandio, Ghulam Asghar Chandio, Bharat Lai, Waseem Raja, Shehzad Memon Sardar Khatoon, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2018)
Objective: To detect the frequency of Hepatocellular Carcinoma (HCC) and its association with viral and non-viral risk factors at a tertiary care hospital. Methods: this cross sectional study was conducted in the department of Medicine Unit-1, Peoples University of Medical and Health Sciences (PUMHS) Nawabshah.. 2 years data from January 2016 to December 2017 was initially assessed from medical OPD and medical department of PlIMIIS and NORIN caner hospital Nawabshah. The patients were assessed for HCC in relation to HCV and I IBV. All the demographic and clinical data was collected on a profrma, the results were tabulated and statistically analyzed. Results: Total 70 patients included in this study, 45(64.28°0) were males, 30 (42.85%) had hepatitis C virus ( HCV), 20(28_570 hepatitis B virus (HI3V). 10 (14.28 01patients had both types and I 0 (14.2g%) patients were negative for viral markers. The patients with hepatitis C. only 6 (8.57) patients developed carcinoma of liver, and among HB V cases, only 3 (4_28%) patients were diagnosed as HCC. Out of 10 patients having both viral markers positive. 2( 2.85%) patients resulted in HCC. Conclusion: It is summed up that the incidence of% iral hepatitis is increased ifmales rather than females and the incidence ofHCC is increased in patients SU !Tering from HCV.